Short-term group schema therapy for mixed personality disorders: a pilot study - Skewes, Sally A.; Samson, Rachel A.; Simpson, Susan G.; van Vreeswijk, Michiel (Frontiers in Psychology, 2015)
Schema Therapy has shown promising results for personality disorders but there is a limited evidence base for group Schema Therapy (ST-g) with mixed personality disorders. The aim of this study was to explore the feasibility, acceptability and preliminary effectiveness of ST-g in a sample of eight participants with mixed personality disorders (with a predominant diagnosis of avoidant personality disorder) and high levels of comorbidity. Treatment was comprised of 20 sessions which included cognitive, behavioural, and experiential techniques. Specific schema-based strategies were chosen for a diagnostically mixed group of personality disorder clients. Six participants attended until end of treatment and two dropped-out before mid-treatment. All outcome measures showed changes with large effect sizes in avoidant personality disorder symptom severity, depression and anxiety levels between pre-therapy and follow-up. Four participants achieved a loss of personality disorder diagnosis at the end of therapy. By follow-up, five participants had achieved a loss of diagnosis, suggesting that participants derived ongoing benefits from the group even after treatment ended. Six participants no longer met criteria for depression at the end of treatment and this was maintained for all participants at six-month follow-up. At follow-up, the majority of participants showed clinically significant change on the GSI. For the SMI maladaptive modes, the majority of participants showed improvement at follow-up. At follow-up 40% of participants showed clinically significant change on the SMI adaptive modes. Qualitative feedback indicates that the group helps to normalize participants’ psychological experiences and difficulties and promotes self-expression and self-disclosure, while reducing disinhibition. Preliminary results suggest that short-term ST-g may benefit those with mixed personality disorders, but generalizability is limited by the small sample size and lack of control group